1994
DOI: 10.1113/jphysiol.1994.sp020444
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of adenosine on electrical activity of frog melanotrophs mediated through A1 purinergic receptors.

Abstract: 1. The effects of adenosine were studied in cultured frog melanotrophs by the patch-clamp technique.2. In cell-attached experiments, most cells responded to adenosine (50 /M) by a reversible inhibition of action current discharges without any apparent desensitization. 3. In whole-cell experiments, adenosine provoked a hyperpolarization accompanied by a depression of spontaneous action potentials and a decrease in membrane resistance. When adenosine was repeatedly applied, tachyphylaxis was observed. Addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Extracellular purines are now recognised as important signalling molecules in a variety of cells/tissues including melanotrophs expressing POMC (18–21). With respect to the corticotroph cells in the pituitary gland, Anand‐Srivastava et al .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular purines are now recognised as important signalling molecules in a variety of cells/tissues including melanotrophs expressing POMC (18–21). With respect to the corticotroph cells in the pituitary gland, Anand‐Srivastava et al .…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological experiments revealed that adenosine inhibits electrical activity-driven Ca 2ϩ transients in GH cell lines (645). In frog melanotrophs, adenosine also inhibits spontaneous electrical activity (646), presumably reflecting the inhibitory action on Ca v channels (647), facilitation of A-type K v channels (151), and/or potentiation of delayed rectifier K ϩ channels (150).…”
Section: Other Pituitary Receptors Linked To the G I/o Signaling Pathwaymentioning
confidence: 99%
“…Until recently, however, little was known about the effects of adenosine on the transient outward A-current (Pan, Osmanovic & Shefner, 1994). In a previous electrophysiological study, we have shown that adenosine and the A, receptor agonist R-PIA inhibit spontaneous action potentials in cultured frog melanotrophs (Mei, Vaudry & Cazin, 1994), suggesting that modulation of potassium conductances could be involved in the mechanism of action of adenosine. In the present report, we explored the possibility that an A-type current exists in frog melanotrophs and that adenosine could activate this current.…”
mentioning
confidence: 99%